Analysis of Islamic Marketing Strategies in Sustaining Business (Case Study of Karang Anyar Chicken Rockets) - S. Purnamasari; Mukminah; Kurniaty; Purnama Rozak (Indonesian Journal of Banking and Financial Technology, 2023)
Today's business competition is getting tougher in the business world, both in  the business of goods and services. So that entrepreneurs to be more creative and innovative in carrying out marketing strategies to maintain business, as well as Rocket Chicken Karang Anyar which always tries to make the business run to servive in the midst of competition as it is today with the strategy it has. The formulition of the problem in this how is Rocket Chicken Karang Anyar’s marketing strategy in maintaining the business? And how is the analysis of Islamic marketing strategies carrid out by Rocket Chicken Karang Anyar in maintaining the business?. The purpose of this research is to find out and analyze how to  the marketing strategy is carried out in an Islamic way in maintaining the business. The research was conducted using qualitative research methods with data collection techniques using observition, interviews snd documentation. From the research conducted, it was found that the marketing strategy carried out by Rocket Chicken Karang Anyar was by maintaining the marketing mix and picking up the ball. Meanwhile, in terms of sharia marketing, Rocket Chicken is in accordance with the characteristics of Islamic marketing, namely being honest.